Angiotensin-(1–7) Suppresses Hepatocellular Carcinoma Growth and Angiogenesis via Complex Interactions of Angiotensin II Type 1 Receptor, Angiotensin II Type 2 Receptor and Mas Receptor - Liu, Yanping (Mol Med, 2015)
We recently confirmed that angiotensin II (Ang II) type 1 receptor (AT(1)R) was overexpressed in hepatocellular carcinoma tissue using a murine hepatoma model. Angiotensin(Ang)-(1–7) has been found beneficial in ameliorating lung cancer and prostate cancer. Which receptor of Ang-(1–7) is activated to mediate its effects is much speculated. This study was designed to investigate the effects of Ang-(1–7) on hepatocellular carcinoma, as well as the probable mechanisms. H22 hepatoma-bearing mice were randomly divided into five groups for treatment: mock group, low-dose Ang-(1–7), high-dose Ang-(1–7), high-dose Ang-(1–7) + A779 and high-dose Ang-(1–7) + PD123319. Ang-(1–7) treatment inhibited tumor growth time- and dose-dependently by arresting tumor proliferation and promoting tumor apoptosis as well as inhibiting tumor angiogenesis. The effects of Ang-(1–7) on tumor proliferation and apoptosis were reversed by coadministration with A779 or PD123319, whereas the effects on tumor angiogenesis were completely reversed by A779 but not by PD123319. Moreover, Ang-(1–7) downregulated AT(1)R mRNA, upregulated mRNA levels of Ang II type 2 receptor (AT(2)R) and Mas receptor (MasR) and p38-MAPK phosphorylation and suppressed H22 cell–endothelial cell communication. Thus, Ang-(1–7) administration suppresses hepatocellular carcinoma via complex interactions of AT(1)R, AT(2)R and MasR and may provide a novel and promising approach for the treatment of hepatocellular carcinoma.